Contribuições psicanalíticas à clínica médica na Atenção Primária em Saúde - Furtado, Nathalia Vidigal (2013)
The present work aims to study the clinical practice performed by medical professionals in the context of services of Primary Health Care and think about some possible contributions from psychoanalysis to the theme, focusing a discussion on the social and subjective aspects that are present in this field of acknowledge. This articulation was built using the bibliography of the area and material of the interview carried out with two physicians and three users/clients of these services. Following the tracks of Balint, our hypothesis is that there will always be, in the relationship of doctor and his patient, a place for psychotherapy, although some contexts have a prominent position. We believe that this is the case of services of Primary Health Care as they involve problems with a unique complexity and the task of understanding them should be pursued before any intervention. It is concluded that this understanding is achieved only when the presence of the patient is considered in a proper manner. This change implies necessarily to recognize, at the same time, the presence of the singularity of the medical profession, without which no change is possible. First, we aim to contextualize clinical practice in the Primary Health Care, highlighting its importance in the process of refocusing the logic of health services, and rescue the method of clinical work, considering the proximity and differences in Medicine and Psychoanalysis. Following, we reflect on the need for a psychotherapeutic dimension in the practice of clinical medicine, the importance of issues of transference in the doctor-patient relationship and the need to recognize the disease as a particular/subjective construction of a subject, conceiving clinical practice as a task of caring and construction of meaning in the face of illness experience. From a psychoanalytical study we discuss the status of the body in Medicine, as well as the social bond present in the clinic, considering some issues present from medical training to clinical practice